Ungkapan Imperatif Terhadap Penggambaran Tokoh pada Game Genshin Impact - Nabila Ailsa Widyawati (IZUMI, 2024)
Genshin Impact is a game with a story and fighting theme, even so linguistic research with Genshin Impact as the source data is almost not found. When a character in Genshin Impact fights, the character utters an expression when launching a power that is divided into two with the names elemental skill and elemental burst. Researchers conducted this study to find out what types of imperative expressions are used by the characters in Genshin Impact and the relationship between these expressions and the portrayal of character characters. The approach used is a descriptive qualitative approach with data collection techniques in the form of listening notes and documentation. The results show that the voice line characters in Genshin Impact use all types of Japanese imperative expressions, namely command expressions (meirei), prohibition expressions (kinshi), request expressions (irai) and invitation expressions (kanyuu). The relationship of imperative expressions to character portrayal shows that these expressions describe a lot of the story background and character identity. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor